Importance of Life-Style Modification through Yoga and Ayurvedic Diet in Parmeha-A Review Article - Kumar, Anil; Sherawat, Surender; Jaiman, Devesh (International Research Journal of Ayurveda & Yoga, 2022)
"Diabetes," which is still regarded as a mystery illness, is quickly spreading around the world. Prameha Roga, who is referenced in Ayurveda, may be associated to diabetes. Prameha is a group of urogenital illnesses characterized by excessively discharging turbid urine. The two main kinds of diabetes mellitus identified by current science are insulin-dependent diabetes (type 1 diabetes) and non-insulin-dependent diabetes (type 2 diabetes). In affluent nations, more than 90% of people with diabetes have type 2 diabetes, and this number is significantly greater in underdeveloped nations. Globally, type 2 diabetes mellitus has emerged as a serious health issue. The WHO estimates that 463 million people worldwide have diabetes in 2019, and that number will rise to 578 million by 2030 and 700 million by 2045. In line with Ayurveda Due to the Kaphakara Nidanas that cause Paremha, all the Doshas become more inflamed, but Kledaka Kapha in liquid form specifically affects Meda, Mamsa Dhatus, and Kledatva. Kleda builds up excessively in the body, causing both Dhatvaagni Mandya and Jaataragni Mandya (digestive fire) (tissue fire). Tissues naturally lose their tone, and eventually Ojus and Basti become vitiated and create Prameha. A suitable food plan is required to stop and manage Prameha. Ayurveda places a high priority on diet and yoga, particularly in Prameha Roga. In order to understand the function that diet, yoga, and lifestyle changes have in the management of Prameha Roga, this literary study has been done.